A decade of developments in chronic heart failure treatment: a comparison of therapy and outcome in a secondary and tertiary hospital setting - Franke, Jennifer; Zugck, Christian; Wolter, Jan Sebastian; Frankenstein, Lutz; Ehlermann, Philipp; Nelles, Manfred; Katus, Hugo; Senges, Jochen (Clinical research in cardiology, 2012)
AimsTo investigate determinants and temporal developments of treatment strategies, 5-year survival and heart transplantation rates between patients treated at secondary and tertiary hospitals.Methods and resultsBaseline characteristics, treatment and follow-up data from 2,023 patients with chronic systolic heart failure due to ischaemic or dilated cardiomyopathy enrolled between 1995 and 2005 (996 patients treated at a secondary hospital vs. 1,027 patients treated at a tertiary hospital) were prospectively compared. Patients treated at the secondary hospital setting were twice as likely to have ischaemic cardiomyopathy compared to the tertiary hospital setting as the underlying cause of heart failure (59.7% vs. 33.0%, respectively) and were almost a decade older (mean age 65.2 vs. 56.7 years, respectively). The use of guideline-recommended therapy increased in both centres over time. In direct temporal comparison, both guideline-adherent pharmacological therapy and device therapy were implemented earlier at the tertiary hospital. Survival rates were significantly lower among patients treated at the secondary hospital (log-rank test P < 0.0001). The combined endpoint of all-cause mortality and heart transplantation, however, was not significantly different after adjustment for differences in baseline characteristics (P = 0.44).ConclusionThis study demonstrates the marked disparity between the patient cohorts with chronic systolic heart failure presenting at secondary and tertiary hospitals. Though patient characteristics—particularly age, aetiology of heart failure and the time of implementation of pharmacological and device treatment of heart failure—differed significantly, after adjustment for differences in baseline characteristics, no substantial difference in the combined endpoint of all-cause mortality and HTX was found during the 5-year follow-up period.
First online: 27 July 2011
Gesehen am 24.04.2018